Analisis Pemasaran Kambing PE Pada Kelompok Tani Samajaya di Kelurahan Landasan Ulin Utara Kota Banjarbaru - Sugiarti Sugiarti; Neni Widaningsih; Siti Dharmawati (Universitas Islam Kadiri, 2023)
Abstract This study aims to determine the chain of marketing channels for PE goats at the Samajaya Farmer Group. Location this research was carried out in the Samajaya Farmers Group, North Landasan Ulin Village, Banjarbaru City. This location was determined by purposive sampling. This research will be conducted for 3 months, from February to April 2022. The sample of breeders used is 18 farmers. The data collected in this study are primary data and secondary data. The observed variables include marketing channels and marketing margins. The data analysis used is descriptive analysis based on surveys and observations made, and by calculating the share margin for each marketing channel. There are 2 marketing channels for the Samajaya cattle group, namely: Farmer à consumers and farmers à collectors à consumer. The marketing margin of goats to collector traders is Rp. 800,000 while for consumers there is no marketing margin, while Farmer's share for collectors is 68.63% and consumers are 100%. Keywords: Marketing Analysis, PE Goat, Livestock Groups